Masalah Keakuratan Terjemahan Tuturan Karakter Spongebob dalam Komik Amazing Journey dan Terjemahannya - rahmat wisudawanto; dyah retno pratiwi (Universitas Aki, 2015)
This research aims in describing the problem accuracy of translation utterance of Spongebob. It is a qualitative descriptive. The source of data uses Amazing Journey comic written by Stephen Hillenburg and its Indonesian translation by Komik Warna Team. Meanwhile, the data of this research is all of Spongebob utterances. The result of analysis shows that there are 10 (ten) data considered as less accurate and 1 (one) datum belongs to inaccurate translation. The translation accuracy problems in this research is due to the fact that there are inappropriate translation technique, punctuation and incorrect collocation Keyword: translation, utterance, accuracy, comic